New Therapeutic Avenues of mCSF for Brain Diseases and Injuries - Pons, Vincent; Rivest, Serge (Frontiers in Cellular Neuroscience, 2018)
mCSF is a cytokine known to promote the recruitment of macrophages inducing the release of CCL2, a chemokine mobilizing monocytes to sites of inflammation. Additionally, it induces microglia/macrophage proliferation and the polarization of these cells towards a M2-like phenotype, impairing their ability to release proinflammatory factors and toxic mediators, while favoring the release of mediators promoting tissue repair. Another important player is the mCSF receptor CSFR1, which is highly expressed in monocytes, macrophages and microglia. Here we discuss the new interesting therapeutic avenue of the mCSF/CSFR1 axis on brain diseases. More specifically, mCSF cascade might stimulate the survival/proliferation of oligodendrocytes, enhance the immune response as well as modulate the release of growth factors and the phagocytic activity of immune cells to remove myelin debris and toxic proteins from the brain.